2 Statutes at Large of Pennsylvania from 1682 to 1801 ch. 144 sec. 5 at 235-236 (1896) - (:unkn) unknown (My University, 1705)
"And be it further enacted by the authority aforesaid, That if any negro shall presume to carry any guns, swords, pistols, fowling-pieces, clubs or other arms or weapons whatsoever, without his master's special license for the same, and be convicted thereof before a magistrate, he shall be whipped with twenty-one lashes on his bare back." Passed January 12, 1705-6. Allowed to become a law by lapse of time in accordance with the proprietary charter, having been considered bythe Queen in Council, October 24, 1709, and not acted upon.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES